Evaluation of Marine Gravity Anomaly Calculation Accuracy by Multi-Source Satellite Altimetry Data - Liu, Shanwei; Li, Yinlong; Sun, Qinting; Wan, Jianhua; Jiao, Yue; Jiang, Jinghui (Frontiers in Earth Science, 2021)
The purpose of this paper is to analyze the influence of satellite altimetry data accuracy on the marine gravity anomaly accuracy. The data of 12 altimetry satellites in research area (5° N-23° N, 105° E-118° E) were selected. These data were classified into A, B and C three groups according to the track density, accuracy of the altimetry satellites and the differences of self-crossover. Group A contains Cryosat-2, group B includes Geosat, ERS-1, ERS-2 and Envisat, group C comprises T/P, Jason-1/2/3, HY-2A, SARAL and Sentinel-3A. In Experiment I, the 5′×5′ marine gravity anomalies were obtained based on the data of group A, group B and group C, respectively. Compared with the shipborne gravity data, the root means square error (RMSE) of group A, group B and group C were 4.59 mGal, 4.61 mGal and 4.51 mGal, severally. The results show that high-precision satellite altimetry data can improve the calculation accuracy of gravity anomaly and the single satellite Cryosat-2 enable to achieve the same effect of multi-satellite joint processing. In Experiment II, the 2′×2′ marine gravity anomalies were acquired based on the data of group A, group A+B and group A+C, respectively. RMSE of the above three groups were separately 4.29 mGal, 4.30 mGal and 4.21 mGal, the outcomes show that when the spatial resolution is satisfied, adding redundant low precision altimetry data will add pressure to the calculation of marine gravity anomalies and will not improve the accuracy. Effective combination of multi-satellite data can improve the accuracy and spatial resolution of the marine gravity anomaly inversion.